HUBUNGAN PARITAS DAN RIWAYAT HIPERTENSI DENGAN KEJADIAN PREEKLAMSI BERAT (PEB) DI RUANGAN VK RUMAH SAKIT MEDIKA STANNIA KABUPATEN BANGKA - Meria Turnip; Titin Novayanti Dey; Wilda Wahyuni Siregar; Desika Wali Pardede; Ika Nur Saputri (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
Preeclampsia were still a threatening problem in pregnancy, especially in developing countries. In Indonesia, preeclampsia were a high cause of maternal mortality in addition to bleeding and infection. Preeclampsia could cause problems for both the fetus and the mother. The conditions of preeclampsia and eclampsia would adversely affect the health of the fetus due to decreased uteroplacental perfusion, hypovolemia, vasospasm, and damage to endothelial cells of the placental vessels. The exact cause of preeclampsia were not known. There are various risk factors, including parity factors and a history of hypertension. This type of research was a descriptive study with a case control design and using univariate and bivariate data analysis techniques with chi-square test where the population were inpartu mothers in the VK Room of Medika Stannia Hospital, Bangka Regency. Sampling using accidental sampling technique with a significant level of 95% (p 0.05). The results of this study indicate that there was a relationship between parity (p value 0.009) and history of hypertension (p value 0.023) to the incidence of severe preeclampsia. Based on the results of the study, it is hoped that the hospital will be able to control the risk of severe preeclampsia in the mother during pregnancy, especially mothers with primigravida parity and have a history of hypertension.